 4.2. FILTRATORS

60

Cor

a

down

a

and Cor

b

down

b

by the corollary

297

since our filtrator is

filtered. So we have

x

down

a, y

down

b

:

x

t

A

y

=

> ⇐

Cor

a

t

A

Cor

b

=

> ⇔

(by finite join-closedness of the core)

Cor

a

t

Z

Cor

b

=

> ⇔

Z

l

up

a

t

Z

Z

l

up

b

=

> ⇔

(by infinite distributivity)

Z

l

x

t

Z

y

x

up

a, y

up

b

=

> ⇔

x

up

a, y

up

b

:

x

t

Z

y

=

> ⇔

(by finite join-closedness of the core)

x

up

a, y

up

b

:

x

t

A

y

=

> ⇐

a

t

A

b

=

>

.

4.2.13. Filtrators over Boolean Lattices.

Proposition

341

.

Let (

A

;

Z

) be a down-aligned and up-aligned finitely meet-

closed and finitely join-closed distributive lattice filtrator and

Z

be a boolean lattice.

Then

a

\

A

B

=

a

u

A

B

for every

a

A

,

B

Z

.

Proof.

(

a

u

A

B

)

t

A

B

= (

a

t

A

B

)

u

A

(

B

t

A

B

) = (

a

t

A

B

)

u

A

(

B

t

Z

B

) = (

a

t

A

B

)

u

A

>

=

a

t

A

B.

(

a

u

A

B

)

u

A

B

=

a

u

A

(

B

u

A

B

) =

a

u

A

(

B

u

Z

B

) =

a

u

A

=

.

So

a

u

A

B

is the difference of

a

and

B

.

4.2.13.1.

Distributivity for an Element of Boolean Core.

Lemma

342

.

Let (

A

;

Z

) be an up-aligned finitely join-closed and finitely meet-

closed distributive lattice filtrator over a boolean lattice. Then

A

u

A

is a lower

adjoint of

A

t

A

for every

A

Z

.

Proof.

We will use the theorem

108

.

That

A

u

A

and

A

t

A

are monotone is obvious.

We need to prove (for every

x, y

A

) that

x

v

A

t

A

(

A

u

A

x

) and

A

u

A

(

A

t

A

y

)

v

y.

Really,

A

t

A

(

A

u

A

x

) = (

A

t

A

A

)

u

A

(

A

t

A

x

) = (

A

t

Z

A

)

u

A

(

A

t

A

x

) =

>u

A

(

A

t

A

x

) =

A

t

A

x

w

x

and

A

u

A

(

A

t

A

y

) = (

A

u

A

A

)

t

A

(

A

u

A

y

) = (

A

u

Z

A

)

t

A

(

A

u

A

y

) =

⊥t

A

(

A

u

A

y

) =

A

u

A

y

v

y.

Theorem

343

.

Let (

A

;

Z

) be an up-aligned finitely join-closed and finitely

meet-closed distributive lattice filtrator over a boolean lattice. Then

A

u

A

F

A

S

=

F

A

A

u

A

S

for every

A

Z

and every set

S

P

A

.

Proof.

Direct consequence of the lemma.